Displaced Cartilage Within Lymph Node Parenchyma Is a Novel Biopsy Site Change in Resected Mediastinal Lymph Nodes Following EBUS-TBNA. (April 2019) - Doxtader, Erika E.; Pijuan, Lara; Lepe, Marcos; Alex, Deepu; Canepa, Mariana; Deeken, Amy H.; Gibier, Jean-Baptiste; Jain, Deepali; Janaki, Nafiseh; Jelinek, Alexis; Kumar, Sunil; Labiano, Tania; et al.
Abstract : Biopsy site changes in mediastinal lymph nodes (LNs) attributable to prior endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) have not been studied in a systematic manner. Twenty-four contributors from 14 institutions in 5 countries collaborated via social media (Twitter) to retrospectively review consecutive cases of resected mediastinal LNs from patients with prior EBUS-TBNA. Resected LNs were reexamined by submitting pathologists for changes attributable to EBUS-TBNA. Patients who received neoadjuvant therapy were excluded. Cases with suspected biopsy site changes underwent central review by 5 pathologists. A total of 297 mediastinal LN resection specimens from 297 patients (183 male/114 female, mean age: 65 y, range: 23 to 87) were reviewed. Biopsy site changes were most common in station 7 (10 cases) followed by 11R, 4R, and 10R, and were found in 34/297 (11.4%) cases, including displacement of tiny cartilage fragments into LN parenchyma in 26, intranodal or perinodal scars in 7, and hemosiderin in 1. Cartilage fragments ranged from 0.26 to 1.03 mm in length and 0.18 to 0.62 mm in width. The mean interval between EBUS-TBNA and LN resection was 38 days (range: 10 to 112) in cases with biopsy site changes. A control group of 40 cases without prior EBUS-TBNA, including 193 mediastinal LN stations, showed no evidence of biopsy site changes. Biopsy site changes are identified in a subset of resected mediastinal LNs previously sampled by EBUS-TBNA. The location of the abnormalities, temporal association with prior EBUS-TBNA, and the absence of such findings in cases without prior EBUS-TBNA support the contention that they are caused by EBUS-TBNA.